Irreducible anterior shoulder dislocation with interposition of the lesser tuberosity and subscapularis. (April 2021) - Ayoubi, Rami; Najm, Talal; Maalouly, Joseph; Aouad, Dany; Kanj, Vladimir; El Rassi, Georges
Abstract: Anterior shoulder dislocation is the most common joint dislocation, unreducible dislocations however are a rare occurrence. The causes of the irreducibility vary, with interposition of soft tissues or bony fragments within the glenohumeral joint being the usual culprits. We present the case of an irreducible anterior shoulder dislocation with concomitant greater and lesser tuberosity fractures, with interposition of the subscapularis and lesser tuberosity thereby preventing reduction. We present the case of a 54-year-old female presenting with a left shoulder fracture dislocation after a fall from a 1.8-meter ladder. Patient was taken to the operating room after undergoing a CT scan. Attempts of closed reduction after administration of general anesthesia were unsuccessful. Open reduction and internal fixation with plate and screws was done through a deltopectoral approach. Intra-operatively, the lesser tuberosity and the subscapularis were found to be the cause of the irreducibility of the dislocation. At the latest follow up at 6 months post-op, the patient had regained a normal ROM with a good function. The vast majority of shoulder fracture dislocations are easily reducible, with only a limited number of case reports discussing irreducible fracture-dislocations. The causes of the irreducibility comprise interposition of soft tissue or bony fragments within the glenohumeral joint such as avulsed labrum or tendons, glenoid or humeral bony fragments interposition, and tensioning of nerves or tendons such as the biceps or subscapularis around the humeral head. CT scans are in our opinion very important for proper surgical planning when needed and for possible identification of an irreducible dislocation. Orthopedic surgeons should be aware that difficult closed reductions of the glenohumeral joint, whenever encountered, should raise the possibility of interposition of bony fragments or soft tissues where surgical treatment might be mandatory.